(untitled) (Research, Society and Development, 2022)
Objective: To analyze the association between maternal infection during pregnancy and the occurrence of childhood leukemia. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “gestation”, “maternal infection”, “infection”, “infectious”, “bacterial”, “vírus”, "leukemia", "child", "infant" and “neonat”. Full articles, available in English, published between January 2010 and December 2021 and studies with results based on statistical data with associations between the variables of interest provided were included. Results: Seven articles made up the final sample of this study, with the highest frequency of publication in 2016 (n: 02) and the highest production in Sweden (n: 04). All studies used the case-control study methodology, characterizing the studies as presenting a moderate level of evidence (III). Cytomegalovirus infection during pregnancy was found to be associated with an increased risk of childhood leukemia in the offspring, specifically childhood acute lymphoblastic leukemia. The other infectious agents highlighted in the studies, despite showing an increased risk, showed statistically non-significant associations, not being conclusive as to their results. Conclusion: It was found that it is not possible to generalize that maternal infection during pregnancy is statistically associated with the occurrence of childhood leukemia in the offspring, in such a way that only the infectious agent cytomegalovirus showed significant associations. Thus, more robust observational studies need to be carried out in order to verify these relationships in greater detail.